Resident attitudes toward the Rio 2016 Olympic Games: A longitudinal study on social legacy and support behaviours. (March 2022) - Ribeiro, Tiago; Yoda, Ryuta; Papadimitriou, Dimitra A.; Correia, Abel
Abstract: The current study describes changes in Rio resident attitudes regarding perceived social legacy and examines its effect on support behaviours from pre-to post-Games stages. Four random samples of local residents from Rio de Janeiro were surveyed in 2015 (n = 532), 2016 (n = 519), 2017 (n = 465), and 2020 (n = 391). A MANOVA and a series of ANOVA tests were performed to analyse the differences in perceptions in different temporal stages followed by a structural equation analysis. Results showed that perceptions of social legacies and support for Rio 2016 has changed over time, increasing during the Games-time, but gradually going down after the event. Findings confirmed the positive and significant effect of the social legacy as a predictor of resident support for the Games in all four stages.